KINERJA KARYAWAN PT. SUMBER MAS: PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI - Inna Nisawati Mardiani Sadeli (Jurnal Pengembangan Wiraswasta, 2018)
A leader as an individual is a personality dealing with a number of other individuals, each of whom is also a personality. The style of leadership and motivation is important in a modern era where the organization demo democracy in the implementation of work and work motivation is good, a result that may arise from a leadership style and poor motivation is a decline in employee performance that will have an impact on total performance decline company. The problems in the review of the above description can be formulated as follows.Is there any influence between leadership style to the performance of employees of PT. Sumber Mas, is there any influence between the motivation on the performance of employees of PT. Sumber Mas, among the variables - style of leadership and motivation which dominant influence on employee performance. Population in this research is all employees of PT. Sumber Mas 93 people, The sample is determined by proportional random sampling technique, with 75 respondents. Data collection methods used are questionnaire (questionnaire) and documentation. The method of analysis used in this research is multiple linear regression analysis method.Based on the results of the research obtained multiple linear regression equation Y = 22.741 + 0.208 + 0.160 , While from the test partial hypothesis (t test) obtained t count from leadership style variables of 3.373T arithmetic motivation variable as much as 2.832 where the probability is smaller than 0.05 then the hypothesis is received. The coefficient of determination (Adjust R2) of 0.324 is the performance of employees of PT Sumber Mas influenced by the style of leadership and motivation, while the rest is influenced by other variables that are outside the variables in the research.Â Keywords:Leadership Style, Motivation, Employee Performance